The Certainty of Health Students to Receive Covid-19 Vaccination in Jayapura City in 2022 - Ayomi, Mina Blandina (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Covid-19 vaccination among health students is an example of a social change agent or role model. Health students must be certain and able to use their knowledge. As a result, it is vital to investigate the likelihood of health students receiving Covid-19 immunization as a form of government support for the health program from the Republic of Indonesia. Objectives: To find out the certainty of health students to receive the Covid-19 vaccination in Jayapura City in 2022. Methods: A descriptive survey was carried out to perform quantitative research at Cenderawasih University in Jayapura City in August 2022. A total of 270 samples were collected using the probability sampling method. The instrument utilized was a questionnaire containing questions concerning health students' opinions about adopting the Covid-19 immunization, which was delivered via Google form. The data was edited, coded, entered, and tabulated before being presented in tabular form and narrated. SPSS was used to perform a univariate analysis of the data. Results: There were 190 respondents (70.4%) who were confident in receiving the Covid-19 vaccination, whereas there were 80 respondents (29.6%) who were unsure. Fear of adverse effects such as fever and pain was the most common reason for being unsure about the Covid-19 vaccine, cited by 56 respondents (97.5%), while comorbidity was cited by only two respondents (2.5%). Conclusions: There are still health students who are not sure about the Covid-19 vaccination. Health students need KIE (communication, information, and education) among health students regarding the necessity of the Covid-19 vaccine.